Students’ and teachers’opinions about ski lessons taught by using peer teaching model - Ozbal, Ayse Feray; Eski, Tolga (Birlesik Dunya Yenilik Arastirma ve Yayincilik Merkezi, 2019)
The aim of this study is to determine students’ and teachers’ opinions about the ski lessons in which peer teaching model is used. The participants of the study were 12 students as ‘peer teachers’, 16 students as ‘peer learners’ and one academician teaching skiing at a university. The participation was on a voluntary basis. Qualitative research method is used in the research and the data were obtained through semi-structured interviews, and the learner diaries also provided supplementary data. The data obtained were analysed by using content analysis method. The findings revealed that peer teachers improved their teaching and communication skills, and peer learners communicated more comfortably while improving their skills and their questions were answered more effectively. In addition, the analysis of the data obtained from the academician revealed that the time was used more efficiently in ski lessons, and the classroom was managed more easily, so there were more opportunities and time for practice. Keywords: Peer teaching, skiing, teaching, sport, education
Keywords: 4. Education